Respon Siswa terhadap Belajar dari Rumah pada Masa Corona Virus Melalui Pembelajaran Jarak Jauh dalam Jaringan - Mince Rompas (Universitas Tadulako, 2021)
This study aimed to determine students’ responses to Learning from Home during the corona virus era through distance learning network at SMA Karuna Dipa Palu. The method used was a qualitative method with a descriptive qualitative approach, by distributing questionnaires to 11th and 12th graders at SMA Karuna Dipa Palu. Distance Learning Network was carried out using the Zoom application and WhatsApp Group. The results showed that students gave negative response on Learning From Home through Distance Learning Network because: online learning were not interesting and fun because the material was difficult to understand and cannot work together with friends; the assignments given were in the form of independent work, not in groups so that it was ineffective and inactive. Studying at home was worse than at school, because at home there were many things that can interfere with learning such as slow network connection, blackout, the difficulty in asking questions, some lessons were difficult to understand, lack of guidance from teachers, lots of assignments, limited quota, noisy surroundings and there are some lessons that cannot be practiced. Meanwhile the positive response of students' insights was increasing towards the use of technology in learning and making them more independent, preventing the spread of the corona virus, saving transportation costs and pocket money, being closer to family and can help their parents while studying.